Making the transition from traditional to robotic-arm assisted TKA: What to expect? A single-surgeon comparative-analysis of the first-40 consecutive cases - Naziri, Qais (J Orthop, 2019)
OBJECTIVE/METHODS: We compared short-term outcomes following 40 traditional, cemented total knee arthroplasty (TKA) to the first 40 cemented robotic-arm assisted TKA (raTKA) and analyzed the learning curve for raTKA. RESULTS: LOS was longer for traditional TKA compared to raTKA (1.92 vs. 1.27days, p < 0.0001). There was no difference in surgical time between the second 20 raTKA and all traditional TKA cases (81.1 vs. 78.3 mins, p = 0.254). raTKA patients had improved 90-day ROM (+3.8° vs. −8.7°, p < 0.05) but comparable complications rates, Knee Society Scores, and patient-reported outcomes at all timepoints. CONCLUSION: Despite comparable outcomes, the learning curve for raTKA appeared to progress rapidly.